(untitled) (Journal of Philosophy Culture and Political Science, 2018)
The article opens pre-conditions, content and chronologic scopes of modernisation and postmodernisation processes. The Kazakhstan model of political reform can’t be considered without forming of political consciousness and political culture which assist forming of certain type of consciousness and qualificatory behavior practices of individuals that leads the corresponding change of public institutes. No modernisation initiatives worked out on a macrolevel can be productive without forming of new type of personality, being the product of sociocultural modernisation. Key words: political reform, political modernisation, political culture, political consciousness, theory of modernisation, ethnic consent, civil society, system of values.